The trinitarian gift unfolded: sacrifice, resurrection, communion - Griffiths, John Mark Ainsley (2015)
Contentious unresolved philosophical and anthropological questions beset contemporary gift theories. What is the gift? Does it expect, or even preclude, some counter-gift? Should the gift ever be anticipated, celebrated or remembered? Can giver, gift and recipient appear concurrently? Must the gift involve some tangible ‘thing’, or is the best gift objectless? Is actual gift-giving so tainted that the pure gift vaporises into nothing more than a remote ontology, causing unbridgeable separation between the gift-as-practised and the gift-as-it-ought-to-be? In short, is the gift even possible?